2002
DOI: 10.1270/jsbbs.52.193
|View full text |Cite
|
Sign up to set email alerts
|

Breeding of Moricandia arvensis Monosomic Chromosome Addition Lines (2n=19) of Alloplasmic (M. arvensis) Raphanus sativus.

Abstract: By backcrossing to Raphanus sativus cv. 'Pink ball', 55 BC 2 plants were obtained from two sesquidiploidal BC 1 plants (MaRR, 2n = 32) between Moricandia arvensis (MaMa, 2n = 28) and R. sativus (RR, 2n = 18). Their somatic chromosome numbers ranged from 2n = 18 to 2n = 23, except for one hyperploid plant with 2n = 44. In the BC 3 generation, 64 plants (2n = 19) were generated from 16 BC 2 plants with 2n = 19~23. Each plant with 2n = 19 exhibited both morphological and physiological characteristics diagnostic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 23 publications
0
19
0
1
Order By: Relevance
“…rapa MALs generated in the progenies through female and male gametes of the BC 1 hybrids (RRA genome) were 50.9 % and 40.0 %, respectively, although in the BC 1 hybrids (RRA genome) more heterogenetic pairings were observed than in the present BC 1 hybrids (DtRR genome). As for the development of MALs with the genetic background of R. sativus, the proportions of MALs produced through female gametes of the BC 1 hybrids were 25 % for B. oleracea (Kaneko et al 1987) and 20 % for M. arvensis (Bang et al 2002). Matsuzawa et al (1996) classified the five lines with genetic modifications into autoplasmic and alloplasmic ones.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…rapa MALs generated in the progenies through female and male gametes of the BC 1 hybrids (RRA genome) were 50.9 % and 40.0 %, respectively, although in the BC 1 hybrids (RRA genome) more heterogenetic pairings were observed than in the present BC 1 hybrids (DtRR genome). As for the development of MALs with the genetic background of R. sativus, the proportions of MALs produced through female gametes of the BC 1 hybrids were 25 % for B. oleracea (Kaneko et al 1987) and 20 % for M. arvensis (Bang et al 2002). Matsuzawa et al (1996) classified the five lines with genetic modifications into autoplasmic and alloplasmic ones.…”
Section: Discussionmentioning
confidence: 99%
“…Bang et al (1996a) reported similar instances in the reciprocal crossings between M. arvensis and R. sativus, where the F 1 hybrids could not be obtained when R. sativus was used as pistillate parent. However, seven M. arvensis autoplasmic MALs of R. sativus could be produced through male gametes of eight M. arvensis alloplasmic MALs of R. sativus (Bang et al 1997b(Bang et al , 2002. Therefore, if eleven D. tenuifolia alloplasmic MALs of R. sativus were produced from the BC 2 hybrids obtained in this study and then if they displayed pollen fertility, complete sets of eleven D. tenuifolia autoplasmic MALs of R. sativus might be obtained through male gametes of the alloplasmic MALs in addition to the BC 1 hybrids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Fig. 1, M. arvensis MALs of alloplasmic R. sativus having M. arvensis cytoplasm were produced and they were classified into twelve types (MaR-a -l, 2n = 19) by their morphological, physiological and cytological characteristics (Bang et al, 2002). The twelve types have been maintained by backcrossing to R. sativus cv.…”
Section: .Plant Materials and Production Of Mals And Dalsmentioning
confidence: 99%
“…Among the species of Brassicaceae in which C 4 species have not yet been found, other C 3 -C 4 intermediate species have also been found within the genera Moricandia, Diplotaxis and Brassica (Apel et al, 1997). M. ar vensis, which was the first-reported C 3 -C 4 intermediate species in the Brassicaceae (Apel et al, 1978;Holaday et al, 1981), has attracted the attention of breeders because its traits can be introgressed into cultivated crops to improve their photosynthetic efficiency (Apel et al, 1984;Toriyama et al, 1987;Takahata, 1990;Takahata and Takeda, 1990;Kirti et al, 1992;Takahata et al, 1993;Razmjoo et al, 1996;Bang et al, 1996Bang et al, , 2002Bang et al, , 2007Ishikawa et al, 2003).…”
mentioning
confidence: 99%